Ancient aesthetics - Mason, Andrew S. (New York, NY Routledge, 2016)
"Ancient thought, particularly that of Plato and Aristotle, has played an important role in the development of the field of aesthetics, and the ideas of ancient thinkers are still influential and controversial today. Ancient aesthetics introduces and discusses the central contributions of key ancient."
Includes index.
Keywords: Aristotle; Plato; Aesthetics, Classical -- Greece; Art -- Philosophy